THE INFLUENCE OF CHRONIC NON–CALCULOUS CHOLECYSTITIS ON THE COURSE OF CORONARY HEART DISEASE - Vovk, K.V.; Nikolenko, E.Y.; Alexandrova, N.K.; Sokruto, O.V.; Ovcharenko, L.K. (World of Medicine and Biology, 2020)
Diseases of the gallbladder and biliary ducts, particularly, chronic non–calculous cholecystitis is a common pathology of internal organs. In addition, with chronic non-calculous cholecystitis, a reflex disorder of the coronary blood circulation, metabolic and autoimmune dystrophic lesions of the myocardium and its conduction system, which can affect the contractile function and heart rhythm, are found. Significant prevalence of these two diseases, high level of work incapacity and disability determine the relevance of the problem of the combined course of these diseases. The purpose of the work was to determine the characteristics of the course of coronary heart disease with concomitant chronic non–calculous cholecystitis, taking into account the functional state of the cardiovascular system. The total of 88 patients who were on outpatient treatment was examined. The clinical course of stable effort angina of functional classes I and II with concomitant chronic non–calculous cholecystitis is characterized by more pronounced clinical manifestations of cardiac pathology, an increase in resistance to drug treatment, and a decrease in exercise tolerance. Coronary heart disease without hronic non–calculous cholecystitis occurs as an independent disease and is not accompanied by changes in the biliary system. Lipid peroxidation enhancement plays a role in increasing the clinical manifestation of coronary heart disease with concomitant inflammation of the gallbladder. Complication of the clinical course of coronary heart disease with simultaneous chronic non–calculous cholecystitis correlates with more pronounced atherogenic lipid metabolism, activation of lipid peroxidation processes and antioxidant protection deficiency in the blood, impaired hemostasis and inhibition of the heart contractile function. Chronic non-calculous cholecystitis significantly complicates the course of coronary artery disease with stable angina of functional classes I–II: more pronounced changes in the lipid spectrum, indicating the rapid development of atherosclerosis, combination of pain in the heart and right hypochondrium, severe dyspeptic syndrome.
Keywords: coronary heart disease; chronic non–calculous cholecystitis; lipid peroxidation; stable angina; antioxidant protection